PERFORMANCE ANALYSIS OF EMPLOYEES THROUGH TRAINING AND DEVELOPMENT AT LOCAL DISASTER MANAGEMENT OFFICES (KPBD) INDRAGIRI HULU DISTRICT - Abdul Hairudin; Sry Windartini (JURNAL MANAJEMEN DAN BISNIS, 2021)
Government agencies need employees who have high job performance in order to achieve the desired goals. One aspect that can support the success of employees in achieving work success is through training and development. Likewise, employees do to improve their performance at work.To carry out the Main Tasks and Functions within the Regional Disaster Management Office (KPBD) of Indragiri Hulu Regency, it is supported by 95 employees consisting of 44 civil servants and 51 temporary workers. In this study, the authors used quantitative and qualitative description analysis methods. Quantitative is a way to emphasize the aspect of deep understanding of a problemThe results of the research need to conduct a performance analysis, training and development by agency leaders at the Regional Disaster Management Office (KPBD) Indragiri Hulu Regency. In order to improve performance, skills and skills according to the agency's objectives. Researchers hope that the KPBD of Indragiri Hulu Regency must prepare and complete the equipment for every training and development held at this time.